Keterlibatan Orang Tua Dalam Administrasi Pendidikan Anak Usia Dini - Armanila Armanila; Yasmina Fajri; Nurhayati Nurhayati; Nayla Rizka Irwani; Novia Rahmawati (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to provide a comprehensive understanding of the various forms of parental involvement in supporting early childhood education, while identifying the facilitating and hindering factors for the success of parental involvement programs. Findings from this study illustrate the prevailing perception among parents that still places teachers as the primary determinants of a child's success, despite the significant role parents play as the primary educators for young children. Awareness of this challenge prompted the researcher to delve into more detailed and in-depth investigations.The research results delineate diverse forms of parental involvement, encompassing the supervision of children's study time, financial contributions through donations of toys and books, participation in school meetings, involvement in social service activities, and the repair of play equipment at school. Despite the existence of organized excursions, not all schools can conduct them due to significant cost constraints.Supporting and inhibiting factors in parental involvement encompass economic aspects, time constraints, the level of parental trust in teachers, and the lack of parental involvement programs initiated by schools. These findings offer valuable insights for enhancing parental participation in early childhood education by addressing and optimizing these factors, ultimately creating a more inclusive and empowered educational environment. Keywords: forms of parental involvement; early childhood education.